To return permanently or to return temporarily? Explaining migrants' intentions. (2nd January 2017) - Bilgili, Özge; Siegel, Melissa
Abstract : This paper explores migrants' intentions to return to their origin country on either a permanent or temporary basis. The issue of return has played a key role in the debate on migration and development, but the role of temporary return in this process has seldom been addressed. We expand on the notion of return as an event or process that can be either permanent or temporary in nature, with both forms of return contributing to development processes. Using survey data from Afghan, Burundian, Ethiopian and Moroccan migrants in The Netherlands ( N  = 2745), we study how migrants' experiences in countries of origin and destination are linked to their return intentions. We show that there are significantly more people interested in temporary than permanent return. Plus, while economic integration has no clear link with return intentions, individuals with lower socio-cultural integration are more likely to intend to return permanently. Moreover, social engagement in the homeland consistently positively relates to intentions for all types of return. Considering the potential positive impact of (temporary) return on development, this research provides insight into the profile of potential return migrants who could be facilitated to return by programs and policies that promote return for development.